Conceptual Framework of Energy Dissipation During Disintegration in Rock Avalanches - Knapp, Sibylle; Krautblatter, Michael (Frontiers in Earth Science, 2020)
Rock avalanches usually progress through three consecutive phases: Detachment (Phase 1), Disintegration (Phase 2) and Flow (Phase 3). While significant advances have been achieved in modelling Rock Avalanche Phase 1 (Detachment) and Phase 3 (Flow), the crucial link between both during Phase 2 (Disintegration) is still poorly understood. Disintegration of the detached rock mass is often initiated as soon as sliding starts, and in-situ measurements are impossible due to the excessive energy release equivalent to multiple nuclear explosions. Better understanding the energy dissipation during Phase 2, and the resulting residual kinetic energy that propels the rock avalanche in Phase 3, is one of the keys to defining the mechanical properties of the avalanche in the runout zone and thus also the resisting force within the avalanche. This paper is a review of our knowledge of energy dissipation in rock avalanches with a focus on processes like friction, collision, fragmentation, comminution, entrainment and explosion during the phase of disintegration. We distinguish between energy sources and sinks and consider not only physical processes, but also chemical alterations that might occur at high temperatures. With that, we make a contribution to improve our understanding of Phase 2 “Disintegration”, which is needed for accurately modelling rock avalanches and assessing their hazard potential.